2018
DOI: 10.1242/dev.154393
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the distribution of stem/progenitor cells across the mouse middle ear during homeostasis and inflammation

Abstract: The middle ear epithelium is derived from neural crest and endoderm, which line distinct regions of the middle ear cavity. Here, we investigate the distribution of putative stem cell markers in the middle ear, combined with an analysis of the location of label-retaining cells (LRCs) to create a map of the middle ear mucosa. We show that proliferating cells and LRCs were associated with specific regions of the ear epithelium, concentrated in the hypotympanum at the base of the auditory bulla and around the ear … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
29
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 32 publications
(61 reference statements)
4
29
0
Order By: Relevance
“…This gene signature is consistent with our previous IF studies which showed the presence of ciliated, secretory and basal cells in the cultures [16]. This in vitro data is also consistent with in vivo studies which have shown the presence of cuboidal epithelial cells expressing secretory proteins alongside regions of ciliated cells [6,7]. Although some of the ciliated cell signature genes are reasonably well studied such as; Spata18 [41] and Cdhr3 [42], none have been identified in the ear previously.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…This gene signature is consistent with our previous IF studies which showed the presence of ciliated, secretory and basal cells in the cultures [16]. This in vitro data is also consistent with in vivo studies which have shown the presence of cuboidal epithelial cells expressing secretory proteins alongside regions of ciliated cells [6,7]. Although some of the ciliated cell signature genes are reasonably well studied such as; Spata18 [41] and Cdhr3 [42], none have been identified in the ear previously.…”
Section: Discussionsupporting
confidence: 92%
“…The mucosal lining of the middle ear cavity covers the entire surface and varies according to the location [6,7]. Cellular morphology can be simple squamous, cuboidal or columnar depending on the location and can have tracts of ciliated cells interspersed with secretory cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Lineage tracing experiments suggest that the inner layer of the pars tensa is derived from first pouch endoderm and is thus continuous with middle ear mucosa (Thompson & Tucker, 2013). Keratin 5 (K5) positive cells have been identified in the basal layer of the middle ear mucosa and play a role in adult middle ear epithelial maintenance (Luo et al, 2017;Tucker et al, 2018). Interestingly, a combination of scRNAseq and lineage tracing has highlighted Keratin 19 (K19) as a marker of mucosal stem/progenitor cells in the murine TM, rather than K5 (Frumm et al, 2019).…”
Section: The Unexplored Inner Mucosal Layermentioning
confidence: 99%